Amos 6:1-7 as an intensification of Amos 3:9-11 - S. D. Snyman (In die Skriflig, 1994)
The composition of the book of Amos has caused a lively discussion in which many different answers have been given. One of the many proposals, namely that of J. Jeremias, holds that Amos 3-4 (a Gotteswort) should be separated from Amos 5-6 (a Prophetenwort), with 3-4 seen as representing, an earlier stage in the formation of the book. In this contribution the proposal made by Jeremias is put to the test by examining two pericopes in Amos 3-6 i.e. 3:9-11 and 6:1-7. The result of the investigation leads to the conclusion that Amos 6:1-7 serves as an intensification of Amos 3:9-11, thereby confirming the results of Jeremias on the composition of the book of Amos.